A bicortical pedicle screw in the caudad trajectory is the best option for the fixation of an osteoporotic vertebra: An in-vitro experimental study using synthetic lumbar osteoporotic bone models. (February 2020) - Shibasaki, Yasuyuki; Tsutsui, Shunji; Yamamoto, Ei; Murakami, Kimihide; Yoshida, Munehito; Yamada, Hiroshi
Abstract: Background: In pedicle screw fixation, the optimal depth and trajectory of insertion are controversial, and this might be because of the wide variations in specimens. The present study aimed to investigate the biomechanically optimal depth and trajectory of screw insertion using synthetic lumbar osteoporotic vertebrae. Methods: A total of 27 synthetic osteoporotic lumbar vertebrae (L3) were used to ensure standard vertebral quality and shape. Pedicle screws having two different lengths (unicortical: to the center of the vertebra; bicortical: to the anterior cortex of the vertebra) were inserted in the following three different trajectories: 1) straight-forward (parallel to the superior endplate), 2) cephalad (toward the anterosuperior corner), and 3) caudad (toward the anteroinferior corner). Maximum insertional torque and pull-out strength were measured. Findings: For the straight-forward, cephalad, and caudad trajectories, the maximum insertional torque (Ncm) values of unicortical screws were 144.4, 143.1, and 148.9, respectively, and those of bicortical screws were 205.5, 156.2, and 207.8, respectively. The maximum insertional torque values were significantly higher for bicortical screws than unicortical screws ( p < 0.001). Additionally, regarding bicortical screws, the maximum insertional torque values were significantly lower for the cephalad trajectory than other trajectories ( p = 0.002). The pull-out strength (N) values of bicortical screws for the straight-forward, cephalad, and caudad trajectories were 703.3, 783.9, and 981.3, respectively. The pull-out strength values were significantly lower for the straight-forward trajectory than other trajectories ( p = 0.034). Interpretation: A bicortical pedicle screw in the caudad trajectory might be the best option to improve fixation in an osteoporotic lumbar vertebra. Highlights: Optimal pedicle screw insertion into osteoporotic lumbar vertebrae was tested. Synthetic bone models were used to eliminate specimen bias. A bicortical pedicle screw in the caudad trajectory might be the best option.